The cloud-based demand-driven supply chain - Sharma, Vinit, 1974- (Wiley and SAS business series., 2019)
Your road map to bringing any supply chain up to state-of-the-art performance, this practical guidebook quickly puts you in a position to make and influence highly informed decisions on customizing cloud-based strategies to optimize supply-chain performance. --